Monitoring sprinting gait temporal kinematics of an athlete aiming for the 2012 London Paralympics - Lee, J. B.; James, D. A.; Ohgi, Y.; Yamanaka, S. (Procedia Engineering, 2012)
Elite running typically requires performance analysis. This equally applies to able-body and amputee athletes who use prosthetic limbs. Amputee runners with artificial limbs deal with unique situations such as balance and control of the prosthetic. A new lower limb has been developed and performance requires ongoing monitoring. Inertial sensor technology, accelerometers and gyroscopes, were used to measure the limb's development, in particular stride, step, and stance duration. While research has been reported on these variables for able-body athletes, no research has investigated these kinematics from Paralympic athletes using inertial technology. The participant's existing and new prosthetic performance were compared. Performance monitoring of the limb during athlete use is required in order objectively assess the new limb's capabilities.